Where Do They Stand? Deviant Art Institutions and the Liberal Democratic State - Mahony, Emma (Irish Journal of Arts Management and Cultural Policy, 2013)
This paper analyses a case study of the public seminar, What Do You Stand For: Who’s Afraid of Solidarity?, held at the National College of Art and Design, Dublin in 2012, in order to unpick the relationship between visual art institutions and left-wing political ideologies. This paper takes the public seminar, What Do You Stand For: Who’s Afraid of Solidarity?, held at the National College of Art and Design, Dublin in 2012, as a case study for an analysis of the relationship between visual art institutions and left-wing political ideologies. It seeks to contextualise the oppositional practices of its four panellists: Valerie Connor (representing Blue Funk), Mark Garry, Garrett Phelan, and Sarah Pierce, in relation to how they align their practices with the liberal democratic state and the art institutions it funds. The relationship of the state to the politics of resistance that operates against it is the starting point for this analysis. This framework is then mapped onto the art institutional landscape and onto the activities of the panellists. The question then becomes: where do these deviant institutions stand in relation to the state-funded established art institution?